GPD1 and ADH3 Natural Variants Underlie Glycerol Yield Differences in Wine Fermentation - Tapia, Sebastián M.; Cuevas, Mara; Abarca, Valentina; Delgado, Verónica; Rojas, Vicente; García, Verónica; Brice, Claire; Martínez, Claudio; Salinas, Francisco; Larrondo, Luis F.; Cubillos, Francisco A. (Frontiers in Microbiology, 2018)
Glycerol is one of the most important by-products of alcohol fermentation, and depending on its concentration it can contribute to wine flavour intensity and aroma volatility. Here, we evaluated the potential of utilising the natural genetic variation of non-coding regions in budding yeast to identify allelic variants that could modulate glycerol phenotype during wine fermentation. For this we utilised four Saccharomyces cerevisiae strains (WE - Wine / European, SA - Sake, NA - North American, and WA - West African), which were previously profiled for genome-wide Allele Specific Expression (ASE) levels. The glycerol yields under Synthetic Wine Must (SWM) fermentations differed significantly between strains; WA produced the highest glycerol yields while SA produced the lowest yields. Subsequently, from our ASE database, we identified two candidate genes involved in alcoholic fermentation pathways, ADH3 and GPD1, exhibiting significant expression differences between strains. A reciprocal hemizygosity assay demonstrated that hemizygotes expressing GPD1WA, GPD1SA, ADH3WA and ADH3SA alleles had significantly greater glycerol yields compared to GPD1WE and ADH3WE. We further analysed the gene expression profiles for each GPD1 variant under SWM, demonstrating that the expression of GPD1WE occurred earlier and was greater compared to the other alleles. This result indicates that the level, timing, and condition of expression differ between regulatory regions in the various genetic backgrounds. Furthermore, promoter allele swapping demonstrated that these allele expression patterns were transposable across genetic backgrounds; however, glycerol yields did not differ between wild type and modified strains, suggesting a strong trans effect on GPD1 gene expression. In this line, Gpd1 protein levels in parental strains, particularly Gpd1pWE, did not necessarily correlate with gene expression differences, but rather with glycerol yield where low Gpd1pWE levels were detected. This suggests that GPD1WE is influenced by recessive negative post-transcriptional regulation which is absent in the other genetic backgrounds. This dissection of regulatory mechanisms in GPD1 allelic variants demonstrates the potential to exploit natural alleles to improve glycerol production in wine fermentation and highlights the difficulties of trait improvement due to alternative trans-regulation and gene-gene interactions in the different genetic background.